2010
DOI: 10.1590/s0102-86502010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of simvastatin in the cyclophosphamide-induced hemohrragic cystitis in rats

Abstract: PURPOSE: Cyclophosphamide (CYP) is an antineoplastic agent used for the treatment of many neoplastic and inflammatory diseases. Hemorrhagic cystitis is a frequent side effect of CYP. Several studies show that simvastatin has important pleiotropic (anti-inflammatory and immunomodulatory) effects. The purpose of the study was to investigate the effect of simvastatin on bladder, ureter and kidney injury caused by CYP. METHODS: Adult male Wistar rats were randomly divided into three groups. The CYP/SIM group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…The present results indicate that lovastatin has a potent anti-inflammatory activity since it inhibits carrageenan-induced peritonitis and paw edema. Although these findings are consistent with studies showing these effects of statins in many inflammation models, most of them were carried out with other statins, mainly simvastatin (21)(22)(23).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present results indicate that lovastatin has a potent anti-inflammatory activity since it inhibits carrageenan-induced peritonitis and paw edema. Although these findings are consistent with studies showing these effects of statins in many inflammation models, most of them were carried out with other statins, mainly simvastatin (21)(22)(23).…”
Section: Discussionsupporting
confidence: 89%
“…Lovastatin inhibited MPO release in a concentration-dependent manner by 23,79, and 86% at the three concentrations tested, respectively. Indomethacin (35.7 µg/mL) used as a positive control inhibited MPO release by 93%.…”
Section: Effects Of Lovastatin On the Release Of Human Neutrophil Mpomentioning
confidence: 90%
“…Studies showed that lovastatin has a potent anti-inflammatory activity since it inhibits carrageenan-induced peritonitis and paw edema. Although these findings are consistent with studies showing these effects of statins in many inflammation models, most of them were carried out with other statins, mainly simvastatin (Dantas et al, 2010;Massaro et al, 2010;. Studies demonstrate that simvastatin provides a highly effective therapy in treating murine Collagen-Induced Arthritis (CIA), a surrogate model for human Rheumatoid Arthritis (RA).…”
Section: Discussionsupporting
confidence: 78%
“…Hajipour et al (2009) showed that Simvastatin pretreatment reduced intestinal I/R injury and was associated with downregulation of serum TNF- α and tissue malondialdehyde level and Simvastatin administration maintained cellular antioxidant enzyme contents compared to the I/R group after 3-hour reperfusion time [26]. Dantas et al (2010) found that Simvastatin pretreatment attenuated cyclophosphamide-induced urothelium inflammation in an experimental rat model, through significantly reducing plasma level of proinflammatory cytokines (TNF- α , IL-6, and IL-1 β ) [27]. …”
Section: Discussionmentioning
confidence: 99%